Identification of Scientific Argumentation Ability of High School Students on Optical Instrument Material - Amin, Rais Muktamar; Parno, Parno; Kusairi, Sentot; Ali, Marlina (Jurnal Pendidikan Sains, 2023)
Optical instruments play a crucial role in physics education, providing essential material for students to understand complex concepts. This study aims to evaluate the scientific argumentation abilities of high school students regarding optical instruments. Conducted as a quantitative descriptive study, the research involved 60 eleventh-grade MIPA students from SMA Laboratorium UM. The research instrument was a scientific argumentation test comprising 12 essay questions, designed according to the Toulmin Argumentation Pattern (TAP) adaptation indicators, with a reliability coefficient of 0.332. Student responses were classified into five levels of scientific argumentation based on the TAP model, as developed by Sampson, Enderle, and Walker, which includes elements such as claims, data, warrants, backings, and rebuttals. The findings indicate that 33% of students demonstrated scientific argumentation at level 1, 36% at level 2, and 31% at level 3, reflecting varied levels of proficiency in constructing scientific arguments. DOI: https://doi.org/10.17977/jps.v11i42023p142